La poétique du nom dans l’œuvre de José Mauro de Vasconcelos - Samuel Bidaud (Caravelle)
This article aims to study the poetics of the name in the stories of the Brazilian writer José Mauro de Vasconcelos (1920-1984). To name represents indeed an important issue in Vasconcelos’ work, and is part of the characters’ recreation of the world. Moreover, the name can be featured by its fragmentation and reflect an identital as well as an existential rip. Finally, it arouses fascination due to its narrative potentiality, emotional value and the love fetishization it brings about.